Self-assembled cationic organic nanosheets: role of positional isomers in a guanidinium-core for efficient lithium-ion conduction. Issue 41 (5th October 2021) - Dey, Ananta; Ramlal, Vishwakarma Ravikumar; Sankar, Selvasundarasekar Sam; Kundu, Subrata; Mandal, Amal Kumar; Das, Amitava
Abstract : Self-assembled organic nanosheets (SONs) having a near-atomic thickness (∼4.5 nm) are obtained through exfoliation. Among two positional isomers of the guanidinium-core analogue used for SONs, one shows greatly improved Li + ion conductivity. Abstract : The growing energy demand with the widespread use of smart portable electronics, as well as an exponential increase in demand for smart batteries for electric vehicles, entails the development of efficient portable batteries with high energy density and safe power storage systems. Li-ion batteries arguably have superior energy density to all other traditional batteries. Developing mechanically robust solid-state electrolytes (SSEs) for lithium-ion conduction for an efficient portable energy storage unit is vital to empower this technology and overcome the safety constraints of liquid electrolytes. Herein, we report the formation of self-assembled organic nanosheets (SONs) utilizing positional isomers of small organic molecules (AM-2 and AM-3) for use as SSEs for lithium-ion conduction. Solvent-assisted exfoliation of the bulk powder yielded SONs having near-atomic thickness (∼4.5 nm) with lateral dimensions in the micrometer range. In contrast, self-assembly in the DMF/water solvent system produced a distinct flower-like morphology. Thermodynamic parameters, crystallinity, elemental composition, and nature of H-bonding for two positional isomers are established through various spectroscopic and microscopic studies. The efficiency of the lithium-ion conducting properties is correlated with factors like nanostructure morphology, ionic scaffold, and locus of the functional group responsible for forming the directional channel through H-bonding in the positional isomer. Amongst the three different morphologies studied, SONs display higher ion conductivity. In between the cationic and zwitterionic forms of the monomer, integration of the cationic scaffold in the SON framework led to higher conductivity. Amongst the two positional isomers, the meta -substituted carboxyl group forms a more rigid directional channel through H-bonding to favor ionic mobility and accounts for the highest ion conductivity of 3.42 × 10 −4 S cm −1 with a lithium-ion transference number of 0.49 at room temperature. Presumably, this is the first demonstration that signifies the importance of the cationic scaffold, positional isomers, and nanostructure morphologies in improving ionic conductivity. The ion-conducting properties of such SONs having a guanidinium-core may have significance for other interdisciplinary energy-related applications.